2013
DOI: 10.1093/molbev/mst149
|View full text |Cite
|
Sign up to set email alerts
|

Pollen-Specific, but Not Sperm-Specific, Genes Show Stronger Purifying Selection and Higher Rates of Positive Selection Than Sporophytic Genes in Capsella grandiflora

Abstract: Selection on the gametophyte can be a major force shaping plant genomes as 7-11% of genes are expressed only in that phase and 60% of genes are expressed in both the gametophytic and sporophytic phases. The efficacy of selection on gametophytic tissues is likely to be influenced by sexual selection acting on male and female functions of hermaphroditic plants. Moreover, the haploid nature of the gametophytic phase allows selection to be efficient in removing recessive deleterious mutations and fixing recessive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 78 publications
10
109
5
Order By: Relevance
“…Molecules involved in gamete:gamete recognition have been shown to evolve rapidly and to be responsible for specieslevel discrimination in mating interactions (Metz et al, 1998;Clark et al, 2006). Interestingly, it was recently shown that the pollen tube expresses a larger fraction of species-limited genes than other tissues (Arunkumar et al, 2013;Gossmann et al, 2014), which is consistent with the idea that pollen tubes may express species-limited proteins that determine their species-level identity. To address whether groups of genes expressed in reproductive tissues maintain higher rates of sequence diversity, we calculated Col versus Cvi exonic SNP rates and compared them to control rates simulated using 100 sets of randomly selected genes of the same number.…”
Section: Expression Of a Large Family Of Thionin-like Crps Is Myb Depmentioning
confidence: 57%
“…Molecules involved in gamete:gamete recognition have been shown to evolve rapidly and to be responsible for specieslevel discrimination in mating interactions (Metz et al, 1998;Clark et al, 2006). Interestingly, it was recently shown that the pollen tube expresses a larger fraction of species-limited genes than other tissues (Arunkumar et al, 2013;Gossmann et al, 2014), which is consistent with the idea that pollen tubes may express species-limited proteins that determine their species-level identity. To address whether groups of genes expressed in reproductive tissues maintain higher rates of sequence diversity, we calculated Col versus Cvi exonic SNP rates and compared them to control rates simulated using 100 sets of randomly selected genes of the same number.…”
Section: Expression Of a Large Family Of Thionin-like Crps Is Myb Depmentioning
confidence: 57%
“…Second, differentiating it from the female gametophyte (which did not show such preferential retention), in an outcrossing species such as maize, pollen and the pollen tube are potentially under more stringent selection than other phases of the life cycle, via intense competition as a haploid for efficient pollen tube germination, tip growth and fertilization processes. Consistent with this idea, pollen-specific genes in an outcrossing relative of Arabidopsis (Capsella grandiflora) are associated with stronger purifying selection and greater proportion of adaptive substitutions than sporophytespecific genes [78]. In this interpretation of gene balance, one would expect to see a larger percentage of pollencritical genes to be retained as duplicates in maize, and furthermore, that mutation of either copy should result in a deleterious phenotype.…”
Section: Discussionmentioning
confidence: 91%
“…Second, these tissues may experience fast evolutionary rates due to their haploid nature and the strong selection forces they undergo and are associated with sexual selection and sperm/pollen competition. Thus, these tissues may appear as evolutionarily accommodating, welcoming and tolerating genomic and functional innovations such as new genes (Bernasconi et al, 2004;Kaessmann, 2010;Arunkumar et al, 2013). More importantly, both methylation levels and the abundances of active histone modifications in promoter regions are significantly and temporally associated with the ages of duplicate genes.…”
Section: Discussionmentioning
confidence: 99%